Crystal structure of PHYHD1A, a 2OG oxygenase related to phytanoyl-CoA hydroxylase. - Zhang, Z; Kochan, G; Ng, S; Kavanagh, K; Oppermann, U; Schofield, C; McDonough, M (2011)
Phytanoyl-CoA hydroxylase (PAHX) catalyzes an important step in the metabolism of the fatty acid side chain of chlorophyll. PHYHD1 exists in three isoforms and is the closest human homologue of PAHX. We show that like PAHX, the PHYHD1A but likely not the PHYHD1B/C isoforms, is a functional Fe(II) and 2-oxoglutarate (2OG) dependent oxygenase. Crystallographic and biochemical analyses reveal that PHYHD1A has the double-stranded β-helix fold and Fe(II) and cosubstrate binding residues characteristic of the 2-oxoglutarate dependent oxygenases and catalyzes the conversion of 2-oxoglutarate to succinate and CO(2) in an iron-dependent manner. However, PHYHD1A did not couple 2OG turnover to the hydroxylation of acyl-coenzyme A derivatives that are substrates for PAHX, implying that it is not directly involved in phytanoyl coenzyme-A metabolism.